Hereditary haemorrhagic telangiectasia and pregnancy: a review of the literature - Dupuis, Olivier (Orphanet J Rare Dis, 2020)
BACKGROUND: Hereditary haemorrhagic telangiectasia (HHT) is a dominantly inherited genetic vascular disorder that has prevalence of 1:5000 to 1:8000, and which is characterised by recurrent epistaxis, cutaneous telangiectasia, and arteriovenous malformations (AVMs) that affect many organs including the lungs, gastrointestinal tract, liver, and central nervous system. The aim here was to carry out a review of the literature on HHT complications during pregnancy in order to guide management decisions. MAIN BODY: A literature review was carried out to analyse all publications on complications that occurred during pregnancy in women with HHT. The PubMed/Medline and Scopus databases were searched. The complications observed in HHT women during pregnancy were then described. The authors identified 5 case series and 31 case reports that describe the evolution of 1577 pregnancies in 630 women with HHT. The overall maternal death rate described in the case series was estimated at 1.0% of pregnancies in the case series and 2 maternal deaths occurred in 31 pregnancy case reports. Severe maternal complications occurred in 2.7 to 6.8% of pregnancies in the case series. Severe complications occurred mostly in the second and third trimester in non-diagnosed and non-screened HHT patients. Severe complications were related to visceral involvement. The most frequent complications were related to pulmonary arteriovenous malformations (PAVMs) (haemothorax (n = 10), haemoptysis (n = 4), and severe hypoxaemia (n = 3)). Neurological complications were related to PAVMs in one case (right to left shunt) and to cerebral arteriovenous malformations (CAVM) and intracranial haemorrhage in 2 cases. Complications were related to hepatic arteriovenous malformations (HAVMs) in 8 cases (acutely decompensated heart failure due to hepatic involvement (n = 1), dyspnoea related to heart failure (n = 5), and hepatobiliary necrosis (n = 2)). CONCLUSION: Based on the literature review, most pregnancies in HHT women occur normally. However, these pregnancies should be considered high-risk, given the potential life-threatening events related to AVM rupture. Furthermore, there is currently no international consensus regarding the medical follow-up of pregnancy in women with HHT and the aim here was to carry out a review of the literature in order to guide screening and management decisions for this rare disease.